Repetitive transcranial magnetic stimulation for cerebellar ataxia: a systematic review and meta-analysis - Yin, Lianjun; Wang, Xiaoyu; Chen, Lianghua; Liu, Dandan; Li, Haihong; Liu, Zhaoxing; Huang, Yong; Chen, Junqi (Frontiers in Neurology, 2023)
Background: Repetitive transcranial magnetic stimulation, a non-invasive brain stimulation technique, can manage cerebellar ataxia (CA) by suppressing cerebral cortical excitability. Hence, this study aimed to summarize the efficacy and safety of rTMS for CA patients by meta-analysis.Methods: PubMed, Embase, Web of Science, and Cochrane Library databases were searched for eligible studies published until May 20, 2023. Weighted mean difference (MD) and 95% confidence intervals (CIs) were utilized to assess the effect of rTMS treatment. Additionally, the quality of the included studies and the risk of bias was evaluated using the Physiotherapy Evidence Database (PEDro) scale.Results: Eight studies involving 278 CA patients were included in this meta-analysis. rTMS could significantly improve the Scale for the Assessment and Rating of Ataxia (SARA) (MD: -2.00; 95%CI: -3.97 to -0.02, P = 0. 05), International Cooperative Ataxia Rating Scale (ICARS) (MD: -3.96; 95%CI: -5.51 to -2.40, P < 0.00001), Timed Up-and-Go test (TUG) (MD: -1.54; 95% CI: -2.24 to -0.84, P < 0.0001), 10-m walk test (10MWT) (MD10-m steps: -2.44; 95%CI: -4.14 to -0.73, P = 0.005), and Berg Balance Scale (BBS) (MD: 2.59; 95%CI: 1.15 to 4.03, P = 0.0004) as compared to sham stimulation. Active rTMS was not significantly different from sham rTMS in changing the duration (MD 10-m time: -1.29; 95%CI: -7.98 to 5.41, P = 0.71). No severe adverse events were observed in both sham stimulation or active rTMS groups.This meta-analysis provides limited evidence that rTMS may be beneficial in treating CA patients. However, these findings should be treated with caution due to the limitations of the small sample size and the inconsistent approach and target of rTMS treatment. Therefore, more largescale RCTs are required to further validate our analytical findings.